2018
DOI: 10.12998/wjcc.v6.i10.344
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal toxicity induced by microcystins

Abstract: Microcystins (MCs) are produced by certain bloom-forming cyanobacteria that can induce toxicity in various organs, including renal toxicity, reproductive toxicity, cardiotoxicity, and immunosuppressive effects. It has been a significant global environmental issue due to its harm to the aquatic environment and human health. Numerous investigators have demonstrated that MC exposure can induce a widespread epidemic of enterogastritis with symptoms similar to food poisoning in areas close to lakes. Both in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Some previous studies have confirmed hepatotoxicity, neurotoxicity, gastrointestinal toxicity, and reproductive toxicity of MC-LR [29][30][31][32]. However, the study of nephrotoxicity induced by prolonged oral exposure to MC-LR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have confirmed hepatotoxicity, neurotoxicity, gastrointestinal toxicity, and reproductive toxicity of MC-LR [29][30][31][32]. However, the study of nephrotoxicity induced by prolonged oral exposure to MC-LR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that animals and humans are mainly exposed to MC-LR through drinking polluted water, body contact, hemodialysis, consumption of contaminated food and algal dietary supplements [8,9,10]. When MC-LR is ingested, it first enters the intestine where most of these toxins are absorbed through the intestinal mucosal barrier (mucosal epithelial cells and mucosal lamina propria), and the absorbed MC-LR are transported through the bloodstream and distributed to the liver and other organs [11]. This may lead to the development of tumor and various acute liver diseases, nervous system damage, gastroenteritis problems and death [4,9,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms for microcystin-induced cell death involve protein phosphatase inhibition, ROS generation, and disruption of the cytoskeleton and calcium homeostasis [ 119 , 120 , 121 , 128 ]. For example, microcystin treatment activated Bid and induced apoptosis in hepatocytes through JNK activation [ 121 ].…”
Section: Microcystin Molecular Toxicologymentioning
confidence: 99%